Cross-sectional evaluation of cognitive functioning in children, adolescents and young adults with ADHD - Marx, Ivo; Hübner, Thomas; Herpertz, Sabine; Berger, Christoph; Reuter, Erik; Kircher, Tilo; Herpertz-Dahlmann, Beate; Konrad, Kerstin (Journal of neural transmission, 2010)
Attention-deficit/hyperactivity disorder (ADHD) often persists into adulthood, albeit with changes in clinical symptoms throughout the life span. Although effect sizes of neuropsychological deficits in ADHD are well established, developmental approaches have rarely been explored and little is yet known about age-dependent changes in cognitive dysfunction from childhood to adulthood. In this cross-sectional study, 20 male children (8-12 years), 20 adolescents (13-16 years), and 20 adults (18-40 years) with ADHD and a matched control group were investigated using six experimental paradigms tapping into different domains of cognitive dysfunction.
Online veröffentlicht am 2. Dezember 2009
Gesehen am 23.05.2023